2020
DOI: 10.7150/ijms.42840
|View full text |Cite
|
Sign up to set email alerts
|

Electric field down-regulates CD9 to promote keratinocytes migration through AMPK pathway

Abstract: Endogenous electric field (EF)-directed keratinocytes migration is known to play a key role in the wound re-epithelialization process. Although many molecules and signaling pathways are reported important for directional keratinocytes migration under EF, the underlying mechanism remains unclear. Our previous research found that CD9, a trans-membrane protein, is involved in wound re-epithelialization and CD9 downregulation contributes to keratinocytes migration. In this study, we observed the effect of EF on CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Also, p38/MAPK inhibition increases CD9 expression, thus supressing migration.46 Building off that knowledge, it was also shown that keratinocytes subjected to direct current EFs (200mVmm −1 ) will have their CD9 expression down-regulated via the 5′ adenosine monophosphate-activated protein kinase (AMPK) pathway. 47 These cumulative factors lead us to believe that if keratinocytes are slowed via an inhibited p38/MAPK pathway (increased CD9 expression), then direct current EFs could down-regulate the CD9 and override the migration inhibition via the alternative AMPK pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Also, p38/MAPK inhibition increases CD9 expression, thus supressing migration.46 Building off that knowledge, it was also shown that keratinocytes subjected to direct current EFs (200mVmm −1 ) will have their CD9 expression down-regulated via the 5′ adenosine monophosphate-activated protein kinase (AMPK) pathway. 47 These cumulative factors lead us to believe that if keratinocytes are slowed via an inhibited p38/MAPK pathway (increased CD9 expression), then direct current EFs could down-regulate the CD9 and override the migration inhibition via the alternative AMPK pathway.…”
Section: Resultsmentioning
confidence: 99%
“…74 It was recently shown that an electric field downregulates CD9, promoting keratinocyte migration through the AMPK pathway. 75 We previously demonstrated that a voltage-gated calcium channel is functionally expressed in human epidermal keratinocytes. 76 On the contrary, a healthy skin surface has a negative electrical potential that is generated by keratinocytes, 77 due to the calcium ion concentration gradient in the epidermis.…”
Section: Electric Fieldsmentioning
confidence: 99%
“…Moreover, during the wound‐healing process, electrical stimulation enhanced epidermal keratinocyte proliferation by modulating the p53–SIVA1 interaction 74 . It was recently shown that an electric field downregulates CD9, promoting keratinocyte migration through the AMPK pathway 75 …”
Section: Sensory Systems For Physical Phenomenamentioning
confidence: 99%
“…52 Building off that knowledge, it was also shown that keratinocytes subjected to direct current EFs (200 mV mm −1 ) will have their CD9 expression down-regulated via the 5′ adenosine monophosphate-activated protein kinase (AMPK) pathway. 55 The sum of these factors led us to believe that if keratinocytes are slowed via an inhibited p38/MAPK pathway (increased CD9 expression), then direct current EFs could down-regulate CD9 and override the migration inhibition via the alternative AMPK pathway.…”
Section: Stimulation Promotes Recovery Of Inhibited Keratinocyte Woun...mentioning
confidence: 99%